Local histogram equalization and homomorphic filtering to improve wide-angle stereo disparity computation - Metzner, Sebastian; Ramesh, Rahul; Hausotte, Tino (Forum Bildverarbeitung 2018, 2018)
Dimensional measurements of reflective surfaces are often challenging for optical measurement systems. The use of structured light causes overexposure of the reflective regions, resulting in an incomplete measurement. Stereo vision is an effective alternate to optical measurements. Image rectification and disparity map computation steps are used to generate a 3D point cloud which can be used for dimensional measurements. When the stereo vision setup requires cameras at wide angles to the surface normal, the image pairs are affected by varying illumination, once again resulting in bad disparity. In this paper different image processing possibilities are examined at the example of a sheet-bulk metal formed workpiece to obtain an improved disparity map of the overexposed areas of the data set. A newly developed local histogram equalization method improves the disparity map for stereo vision calculations with wide-angle camera setups.<br
Keywords: wide-angle stereo vision; image processing; disparity computation